Serum visfatin concentration and its relationship with sex hormones in obese Saudi women - Alnowihi, Sumaih M.; Al Doghaither, Huda A.; Osman, Nadia N. (International Journal of Health Sciences, 2020)
Background: Visfatin is an adipokine secreted mainly by adipose tissue and has been implicated in obesity. It also mimics the effects of insulin and its expression is hormonally regulated by hormones. Objectives: Serum visfatin concentrations were evaluated in Saudi women of different body weights in order to determine its relationships with sex hormones and obesity-induced insulin resistance (IR) in women in Saudi Arabia. Methods: In this cross-sectional study, 83 healthy Saudi women of different body weights were recruited between 2014 and 2016, from King Abdulaziz University staff and students. They were divided into three groups according to their body mass indexes (BMIs). Anthropometric measurements were recorded for all of the participants. Blood samples were collected to assess the biochemical variables, including glucose, insulin, lipid profile, visfatin, sex hormone binding globulin (SHBG), and sex hormones levels. Results: Obese women exhibited significantly higher blood pressure (BP), glucose, insulin, IR, lipid profile, and visfatin levels than overweight and lean women. However, lean women had significantly higher high-density lipoprotein-cholesterol (HDL)-C, estradiol (E2), luteinizing hormone (LH), and SHBG levels than overweight and obese women. Positive correlations were observed between visfatin levels and waist and hip circumferences, BMI, diastolic BP, systolic BP (SBP) insulin, IR, and LDL-C levels (P < 0.001 – P < 0.05). Negative correlations were observed between visfatin levels and HDL-C, SHBG, LH, and E2 levels (P < 0.001 – P < 0.05). Conclusions: The results of this study revealed that E2 and SHBG concentrations were decreased in obese women, while visfatin levels were increased in obese women with high IR levels. This suggests that visfatin levels and sex hormones interact synergistically with obesity with regard to the IR risk in obese women.